1997
DOI: 10.1152/ajplung.1997.272.2.l197
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C prevents LPS-induced pulmonary vascular injury by inhibiting cytokine production

Abstract: We investigated the effect of activated protein C (APC) on pulmonary vascular injury and the increase in tumor necrosis factor (TNF) levels in lipopolysaccharide (LPS)-treated rats to determine whether APC reduces LPS-induced endothelial damage by inhibiting cytokine production. Intravenously administered LPS (5 mg/kg) induced pulmonary vascular injury, as indicated by an increase in the lung wet-to-dry weight ratio. LPS-induced pulmonary vascular injury was prevented by APC but not by active site-blocked fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
149
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(161 citation statements)
references
References 0 publications
9
149
0
3
Order By: Relevance
“…EPCR precludes leukocyte influx by blocking the integrin CD11b/ CD18, as its deficiency induces neutrophilic infiltration and enhanced chemokine production in LPS-challenged mice compared with wild-type animals (71). In experimental endotoxininduced inflammation, activated PC inhibits pulmonary vascular injury by inhibiting TNF-␣ release (72) and limits accumulation of activated leukocytes (73). In human EC-based in vitro systems, activated PC modulates expression of genes related to anti-inflammatory and cell survival pathways, including inhibition of NF-B binding to target sites and multiple NF-B-regulated genes, such as cytokines, chemokines, and adhesion molecules (74,75).…”
Section: Ecs In Coagulation and Inflammationmentioning
confidence: 99%
“…EPCR precludes leukocyte influx by blocking the integrin CD11b/ CD18, as its deficiency induces neutrophilic infiltration and enhanced chemokine production in LPS-challenged mice compared with wild-type animals (71). In experimental endotoxininduced inflammation, activated PC inhibits pulmonary vascular injury by inhibiting TNF-␣ release (72) and limits accumulation of activated leukocytes (73). In human EC-based in vitro systems, activated PC modulates expression of genes related to anti-inflammatory and cell survival pathways, including inhibition of NF-B binding to target sites and multiple NF-B-regulated genes, such as cytokines, chemokines, and adhesion molecules (74,75).…”
Section: Ecs In Coagulation and Inflammationmentioning
confidence: 99%
“…For example, in the THP-1 monocytic cell line and in peripheral blood monocytes, activated protein C down-regulates TNF (9 -11), IL-1␤, IL-6, and IL-8 (12), presumably by inhibiting NF-B nuclear translocation (10) and/or down-regulating the transcription of NF-B subunits (13). In vivo studies of animals challenged with endotoxin have shown that activated protein C prevents the production of proinflammatory cytokines (14,15) and inhibits leukocyte accumulation in injured tissues (16).…”
mentioning
confidence: 99%
“…More recently, activated protein C has been shown to inhibit inflammation (13)(14)(15)(16)(17)(18), apoptosis (19 -22), and to prevent increases in vascular permeability (23,24). With respect to its antiinflammatory properties, activated protein C has been shown to down-regulate the production of TNF by monocytes (13)(14)(15) and to suppress expression of leukocyte adhesion molecules in endothelial cells (16), presumably by inhibiting NF-B nuclear translocation (14) and/or down-regulating the transcription of NF-B subunits (16).…”
mentioning
confidence: 99%
“…With respect to its antiinflammatory properties, activated protein C has been shown to down-regulate the production of TNF by monocytes (13)(14)(15) and to suppress expression of leukocyte adhesion molecules in endothelial cells (16), presumably by inhibiting NF-B nuclear translocation (14) and/or down-regulating the transcription of NF-B subunits (16). In animals challenged with endotoxin, activated protein C inhibited the production of proinflammatory cytokines (17,18) and inhibited leukocyte accumulation in injured tissue (25). Likewise, the PROWESS trial revealed that recombinant activated protein C infusion reduced levels of IL-6, a proinflammatory cytokine (4).…”
mentioning
confidence: 99%